Ready or not! - Bryant, Megan E. (Bryant, Megan E. Abby in between, 2022)
Nine-year-old Abby McAdams is grappling with life adjustments as she starts fourth grade. Her best friend and cousin Zoe is moving away, her dad lost his job and her mom is going back to work, and her body is going through changes. As she tries to make sense of wearing deodorant and other embarrassing conversations, and changes in her family's routine, she discovers a problem of homelessness in her community and decides to take action. Abby learns that while dealing with change can be uncomfortable, some change is good.